Association of genetically determined chronotype with circulating testosterone: a Mendelian randomization study - Ichikawa, Tomohiro; Kobayashi, Takuro; Hachiya, Tsuyoshi; Ikehata, Yoshihiro; Isotani, Shuji; Ide, Hisamitsu; Horie, Shigeo (Frontiers in Endocrinology, 2024)
Low testosterone levels in men have been linked to decreased physical and mental function, as well as a reduced quality of life. Previous prospective observational studies have suggested an association between testosterone and sleep traits, but the causality nature of this relationship remains unclear. We aimed to explore the potential causal link between genetically determined sleep traits and testosterone levels in men using Mendelian Randomization (MR) analysis from the UK biobank dataset. Our exposures were genetic variants associated with sleep traits (chronotype and sleep duration), while our outcomes were traits of sex steroid hormones (total testosterone, TT; bioavailable testosterone, BAT; and sex hormone-binding globulin, SHBG). We employed inverse variance weighted (IVW) and weighted median (WM) methods to assess the causal associations. The IVW method offers a robust estimate of causality, while the WM method provides reliable results even when some genetic variants are invalid instruments. Our main analysis involving sex steroid hormones and chronotype identified 155 chronotype-related variants. The primary findings from the analysis, genetically predicted chronotype score was significantly associated with an increased levels of TT (association coefficient β, 0.08; 95% confidence interval [CI], 0.02-0.14; P=0.008) and BAT (β, 0.08; 95% CI, 0.02-0.14; P=0.007), whereas there was no significant association with SHBG (β, 0.01; 95% CI, -0.02-0.03; P=0.64). Meanwhile, MR analysis of sex steroid hormones and sleep duration was performed, and 69 variants associated with sleep duration were extracted. There were no significant association between sleep duration and sex steroid hormones (TT, P=0.91; BAT, P=0.82; and SHBG, P=0.95). Our data support a causal association between chronotype and circulating testosterone levels in men. These findings underscore a potential causal relationship between chronotype and testosterone levels in men, suggesting that lifestyle adjustments are crucial for men’s health. Recognizing factors that influence testosterone is essential. One limitation of this study is the use of one-sample MR, which can introduce potential bias due to non-independence of genetic associations for exposure and outcome. In conclusion, our findings indicate that a morning preference is correlated with circulating testosterone levels, emphasizing the potential impact of lifestyle habits on testosterone levels in men.